Upscaling of an Innovative Cogeneration CSP System - Poullikkas, Andreas (2013)
An upscaling of an innovative concentrated solar power (CSP) technology for the cogeneration of electricity and desalinated water (CSP-DSW) to be integrated into the Cyprus power generation system is carried out. Further, a comparative study of the competitiveness of the CSP-DSW technology with the integration of natural gas combined cycle (CCGT) technology is carried out. For the simulations, the IPP v2.1 software is used for calculating the optimum cost of electricity produced from both conventional and CSP-DSW technologies. The results indicate that for high capacity factor levels, the CSP-DSW technology scenarios are more cost effective than the CCGT technology (base case natural gas technology price projection scenario) and become even more cost effective at very high capacity factor levels than the CCGT technology (low natural gas technology price projection scenario).